Molecular signatures underlying heterogenous hypertrophy responsiveness to resistance training in older men and women: a within-subject design - Lixandrão, Manoel E.; Bamman, Marcas; Lavin, Kaleen M.; Longobardi, Igor; Telles, Guilherme; Vechin, Felipe C.; Damas, Felipe; Drummer, Devin J.; McAdam, Jeremy S.; Riani Costa, Luiz A.; Libardi, Cleiton A.; Gualano, Bruno; et al. (Journal of applied physiology (1985), 2025)
We showed higher resistance training (RT) volume (4-sets) offsets muscle hypertrophy non-responsiveness to single-set RT (1-set), while enhancing hypertrophic response among responders. Here, we investigated molecular traits underpinning RT-related hypertrophic variability via targeted (ribosome density and biogenesis) and untargeted approaches (RNAseq gene-ontology (GO) and Pathway-Level Information ExtractoR [PLIER]). Twenty-seven older (693 years) participants in the parental trial had one leg randomly allocated to 1-set and the contralateral leg allocated to 4-sets of RT for 10-wk, 2x/week. Pre- and postintervention, participants underwent magnetic resonance imaging (MRI) and muscle biopsies. We selected participants based on quadriceps muscle cross-sectional area (qCSA) changes and used the MRI typical error (2xTE=3.27%) to allocate those in distinct hypertrophy phenotype: low-responders: blunted hypertrophy, regardless of RT-volume; medium-responders: hypertrophy only following the higher RT-volume; and high-responders: hypertrophy following both RT-volume. The qCSA was higher for 4-sets compared with 1-set for medium- and high-responders only. Higher RT-volume, regardless of responsiveness groups, was followed by increased Frizzled-1 protein expression. RNAseq showed that high-responder‘s robust hypertrophy was followed by up-regulation of pathways linked with protein turnover metabolism, RT-related metabolic response, and with protein-folding biological processes. Hypertrophy in medium-responders was marked by down-regulation of pathways linked with muscle catabolism (Proteasome and Spliceosome), modulations on distinct RT-related metabolic response, and biological processes associated with hormone- and steroid-related pathways. Low-responders, on the other hand, did not show measurable changes in any molecular pathways, regardless of RT volume manipulation. Overall, these finding reveal differential molecular signatures across the spectrum of RT responsiveness among older individuals.